Programa nacional de acesso ao ensino técnico e emprego: o curso de agente de desenvolvimento cooperativista sob a ótica dos egressos - Gomes, Vanderlan Bento dos Santos (2017)
In a world of constant change, from agriculture to information technology, the human being has to think about the importance of its social, economic and environmental development in the face of a capitalist system based on competitiveness. In this context, a new form of working philosophy called Cooperative System emerges, organized from the integration of its members, who cooperate and mutually learn and develop their skills. In the Brazilian case, cooperativism has been growing significantly and, in the agricultural sector, it already implies approximately 25% of GDP, according to Embrapa (2014), highlighting the importance and strengthening of this branch in our country. This new form of work is organized from selfmanagement in the perspective of democratic management, training and information of the cooperative. The study was anchored in Paul Singer (2002), in the OCB Cooperative Manual by author Albino Gawlak (2010), organizational learning with Fleury (2007) and Dewey (1979) with Cooperative Education. For this, this research had the role of analyzing the contributions to the students of the Cooperative Development Agent Course of the National Program of Access to Technical Education and Field Employment, held in Guarabira, State of Paraíba, regarding organizational learning and Cooperative. As for the methodological criteria, it is characterized as an exploratory-descriptive case study, supported by a qualitative approach, documental analysis and semi-structured interviews were carried out with 31 students from the Carrasco and Caboclo sites. As for the instruments used to study the processes and products used in qualitative research, Triviños (1995) emphasizes the use of interview in the focus, because at the same time that it values the presence of the researcher, it offers all possible perspectives for the informant to reach Freedom and the necessary spontaneity. Regarding the results, we verified that all the graduates from the Carrasco and Caboclo sites succeeded in their organizational learning, in the practice of rural cooperativism, in which they developed in their formation, collective work and practical dynamics. Concerning the question of the contribution of the course, it is understood its importance for the graduates and the community, in the context of the professional performance after the end of the course. However, these graduates were not able to join the branch of cooperativism, because they did not form cooperatives and did not have support from any entity. Finally, for a better development of the graduates participating in the Cooperative Development Agent course, it is necessary, in fact, a support from an entity that continues the work so that they can put into practice their training after course held in their community of origin . It is intended to leave a legacy in the social, political, academic and institutional field, so that improvements, suggestions and solutions can be proposed to the problems evidenced in the course of the study.